2008
DOI: 10.1017/s1446181108000011
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Generalized Newtonian Lid-Driven Cavity Flow Using an SPH Method

Abstract: In this paper a smoothed particle hydrodynamics (SPH) method is introduced for simulating two-dimensional incompressible non-Newtonian fluid flows, and the nonNewtonian effects in the flow of a fluid which can be modelled by generalized Newtonian constitutive equations are investigated. Two viscoplastic models including Bingham-plastic and power-law models are considered along with the Newtonian model. The governing equations include the conservation of mass and momentum equations in a pseudo-compressible form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…From another point of view, the complexity of constitute equations also inspire researchers to develop some new numerical schemes or methods to study non-Newtonian behaviors. For example, Neofytou proposed a 3rd order upwind finite volume method to study GNF (including the Power-Law fluid, Quemada fluid, Bingham plastics, and Casson fluid) flows in a lid-driven cavity, and validated the method through a comparison with numerical data in available literature [3]; we note that the problem of GNF flows in the lid-driven cavity is also studied recently by Rafiee using smoothed particle hydrodynamics (SPH) method [4]. Bell used a p-version least squares finite element formulation (LSFEF) to investigate two-dimensional, incompressible, Power-law fluid flow under isothermal and non-isothermal conditions, and demonstrated the convergence characteristics and accuracy of the formulation through some numerical examples [5].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…From another point of view, the complexity of constitute equations also inspire researchers to develop some new numerical schemes or methods to study non-Newtonian behaviors. For example, Neofytou proposed a 3rd order upwind finite volume method to study GNF (including the Power-Law fluid, Quemada fluid, Bingham plastics, and Casson fluid) flows in a lid-driven cavity, and validated the method through a comparison with numerical data in available literature [3]; we note that the problem of GNF flows in the lid-driven cavity is also studied recently by Rafiee using smoothed particle hydrodynamics (SPH) method [4]. Bell used a p-version least squares finite element formulation (LSFEF) to investigate two-dimensional, incompressible, Power-law fluid flow under isothermal and non-isothermal conditions, and demonstrated the convergence characteristics and accuracy of the formulation through some numerical examples [5].…”
Section: Introductionmentioning
confidence: 94%
“…The fluid flow in a lid-driven cavity is another classic problem, and has been widely used to validate numerical methods by many authors [3][4][5]37,38] since it has a simple geometry and shows rich vortex phenomena. In this work, this problem is also used to verify the capacity of present MRT model through a comparison between the present numerical results and those reported in some available literature [3,5,37].…”
Section: Power-law Fluid Bingham Plastics and Casson Fluid Flows In mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive reviews can be found in Monaghan 1992 and2005 [10,11]. Recently, SPH has been applied to simulate non-Newtonian and viscoelastic transient and free surface flows, for example see Ellero and Tanner [17], Fang et al [18], Hossein et al [19], Rafiee et al [20] and Rafiee [21].…”
Section: Introductionmentioning
confidence: 99%
“…This benchmark problem has been addressed by some authors [2,22,23,25,28,29]). In the present work, the mechanical model is approximated by multi-field Galerkin least squares method in terms of extra-stress, pressure and velocity.…”
Section: Introductionmentioning
confidence: 99%